Indonesia dalam Menghadapi Pandemi Covid-19 - Ririn Noviyanti Putri (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Indonesia was affected by a new epidemic namely the covid-19 virus. Covid-19 has become a pandemic because the number of confirmed cases in Indonesia continues to increase, so Indonesia urgently needs procedures for controlling and preventing the covid-19 pandemic. This paper aims to analyze the steps Indonesia has taken in dealing with covid-19. The method used by the authors is literature review.The results obtained that Indonesia has implemented many policies in controlling and preventing covid-19. However, the policy must also be supported by public awareness and a good health system.